Preparation of Aligned ZnO Nanorod Arrays on Sn-Doped ZnO Thin Films by Sonicated Sol-Gel Immersion Fabricated for Dye-Sensitized Solar Cell - I. Saurdi; M. H. Mamat; M. F. Malek; M. Rusop (Advances in Materials Science and Engineering)
Aligned ZnO Nanorod arrays are deposited on the Sn-doped ZnO thin film via sonicated sol-gel immersion method. The structural, optical, and electrical properties of the Sn-doped ZnO thin films were investigated. Results show that the Sn-doped ZnO thin films with small grain size (~20 nm), high average transmittance (96%) in visible region, and good resistivity 7.7 × 102 Ω·cm are obtained for 2 at.% Sn doping concentration. The aligned ZnO nanorod arrays with large surface area were also obtained for 2 at.% Sn-doped ZnO thin film. They were grown on sol-gel derived Sn-doped ZnO thin film, which acts as a seed layer, via sonicated sol-gel immersion method. The grown aligned ZnO nanorod arrays show high transmittance at visible region. The fabricated dye-sensitised solar cell based on the 2.0 at.% Sn-doped ZnO thin film with aligned ZnO nanorod arrays exhibits improved current density, open-circuit voltage, fill factor, and conversion efficiency compared with the undoped ZnO and 1 at.% Sn-doped ZnO thin films.